The Effect of Employee Loneliness Towards Work Performance in the Indonesian Workplace Setting - Loran Vincentsius Yeremia; Amie Kusumawardhani (Faculty of Economics and Business Diponegoro University, 2025)
Workplace loneliness is a psychological issue with growing relevance, yet it remains underexplored in Indonesia. This study examines how emotional and social loneliness affect individual work performance in an Indonesian cultural context. Using a quantitative approach, 72 active employees from various sectors completed a structured online questionnaire. The instruments used were the Loneliness at Work Scale (LAWS) and an adapted version of the Individual Work Performance Questionnaire (IWPQ). Data were analysed using linear regression and Spearman correlation. Results indicate that both emotional and social loneliness significantly and negatively influence work performance. The higher the level of perceived loneliness, the lower the performance. These findings highlight the need for Indonesian organisations to foster inclusive and socially supportive work environments.